Becoming Global Asia Contemporary Genres of Postcolonial Capitalism in Singapore - Narumi Naruse, Cheryl (University of California Press, 2023)
Becoming Global Asia centers Singapore as a crucial site for comprehending the uneven effects of colonialism and capitalism. In the wake of the 1997 Asian financial crisis, Singapore transformed its reputation as a culturally sterile and punitive nation to "Global Asia"-an alluring location ideal for economic flourishing. Cheryl Narumi Naruse analyzes how Singapore gained cultural capital and soft power by examining genres such as literary anthologies, demographic compilations, coming-of-career narratives, and princess fantasies. Tracing the trajectory of Singapore's positioning as Global Asia, Naruse reveals how the country emerged as a celebrated postcolonial model nation and a site of imperial desire that enables subjugation of the so-called Third World. Her readings of Global Asia as an invention of postcolonial capitalism offer new conceptual paradigms for understanding postcolonialism, neoliberalism, and empire. "Cheryl Narumi Naruse offers a lucid, much-needed theorization of postcolonial capitalism-a mode of sovereignty simultaneously forged against empire and productive of neoliberal governance. An important and original contribution to debates around Global Asia and its cultural forms, with ramifications far beyond Singapore."- JINI KIM WATSON, Professor of English and Comparative Literature, New York University "After Becoming Global Asia, criticism about cultural geopolitics and literary studies that disregards Singapore, or does not center Naruse's cogent analysis on the aesthetics of postcolonial capitalism, will be incomplete." - MOHAN AMBIKAIPAKER, author of Political Blackness in Multiracial Britain "If you've ever wondered about the dark side of the idea of 'Global Asia,' read this book. And if you are looking for evidence that literature can be more than a mere tool of the state and capital, this book is also for you." - COLLEEN LYE, author of America's Asia: Racial Form and American Literature, 1893-1945"